Tanaman Berus Mata Buaya sebagai Insirasi Motif Batik dalam Busana Kebaya Modern - Septianti, Septianti; Nurviana, Fenty (BAJU: Journal of Fashion and Textile Design Unesa, 2025)
The purpose of designing modern kebaya fashion inspired by the crocodile eye brush plant is as a form of introduction to the crocodile eye brush plant so that people will preserve and cultivate this plant which will later be introduced through batik motifs and applied to modern kebaya fashion. This is because the crocodile eye brush plant is a typical plant from the West Kalimantan Coast which has experienced a population decline due to the surrounding community destroying the habitat of this plant. To create this work, a qualitative descriptive approach method was used with a method of creating craft art with four stages, namely pre-design, design, manifestation, and presentation of the work. Through these stages, 3 fashion designs were produced with batik motifs inspired by the crocodile eye brush plant that were stylized. The three fashion designs have a distinctive feature on the neck with the addition of a tie accent on each dress, and the materials used are brocade and cotton cloth that has been batiked. The batik motif on this dress is applied to the skirt and back of the dress. The batik design displays the characteristics of flowers, leaves, and tendrils on the crocodile eye brush plant and the colors used in this dress are black and green. This creation resulted in three dresses with batik motifs inspired by the crocodile eye brush plant which were realized into modern kebaya dresses.